Efeitos antimicrobianos de extratos de subprodutos do processamento de frutas sobre Escherichia coli enterotoxigênica - Lima, Maiara da Costa (2022)
Enterotoxigenic Escherichia coli (ETEC) is one of the main causes of diarrhea in developing countries. In animals, it causes neonatal diarrheal syndrome, resulting in economic costs and increased risk of food contamination. Fruits used in the Brazilian industry to make food products generate by-products, which are composed of seeds and/or peels, where high concentrations of phenolic compounds are found. The aim of this study was to evaluate the antimicrobial effects of high concentration phenolic extracts from acerola, apple cashew, jabuticaba and mango processing by-products against different strains of enterotoxigenic Escherichia coli. The by-products were obtained from fruit pulp processing companies in the city of João Pessoa. Extracts were prepared (acerola: PEA, apple cashew: PEC, mango: PEM and jabuticaba: PEJ), followed by characterization using high-performance liquid chromatography. The effects of different concentrations of phenolic extracts on the growth of ETEC strains were evaluated by determining the minimum inhibitory and bactericidal concentration (MIC and MBC) and viable cell count. The evaluation of damage induced by phenolic extracts on ETEC cells was evaluated by flow cytometry. Finally, the effect of PEJ exposure on antibiotic susceptibility, autoaggregation, hydrophobicity, biofilm formation and survival under simulated gastrointestinal conditions of different ETEC strains was evaluated. Procyanidin B2, myricetin, p-coumaric acid and cyanidin 3-glucoside were the main phenolic compounds in PEA, PEC, PEM and PEJ respectively. PEA and PEC had lower minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) (MIC: 31.25 mg/mL; MBC: 62.5 mg/mL than PEM (MIC and MIB:> 1000 mg/mL). In PEJ the MIC and MBC were 125 and 250 mg/mL, respectively. PEA and PEC (15.6, 31.2, 62.5 mg/mL) caused reductions in ETEC strain counts after 24 hours of exposure, notably logarithmic reductions ≥3 were caused by 62.5 mg/mL. PEJ exposure at 125 and 250 mg/mL caused reductions in viable cell counts of ≥3 and ≥5 log CFU/mL respectively in ETEC over 24 h. 24-h exposure of ETEC strains to PEA and PEC resulted in the formation of large subpopulations of ETEC cells with concomitant impairments cell membrane polarization and permeability, as well as in enzymatic, respiratory and efflux activities. PEJ at subinhibitory concentrations (31.25 and 62.5 mg/mL) increased the susceptibility of ETEC strains tested to antibiotics, reduced viable ETEC counts when exposed to gastrointestinal conditions in vitro, and decreased biofilm formation, cell surface hydrophobicity, mucin adhesion and motility. Exposure to PEJ (62.5 and 125 mg/mL, 2 h) caused damaged cellular membrane, enzymatic and efflux pump activities in ETEC cells. The results show that PEA, PEC and PEJ effectively reduce ETEC survival, increase susceptibility to antibiotics and attenuate different virulence factors. These outcomes may be linked to a multi-target mode of action of the tested extracts that compromise various cellular functions in ETEC cells by ETEC.